Utilization Of Multimedia-Based Learning In Islamic Cultural History Education Lessons At Integrated Mts Nurul Qodiri Central Lampung - Suwanto, Muhammad; As’ariy, Hasim; Pratiwi, Wiwed (Assyfa Journal of Islamic Studies, 2024)
Learning media are all types of objects and tools that can help the learning process by stimulating thoughts, generating feelings, and increasing students' attention and desire to learn more about the material provided. This results in a learning environment that is intentional, organized, purposeful, and effective under the control of the teacher. The history of Islamic culture consists of three words: history, culture, and Islam. This study was conducted in Kayu Palis Village, Way Pengubuan Regency, Lampung, at the Nurul Qodiri Islamic Boarding School, Central Lampung. Islamic Cultural History lessons at MTs Nurul Qodiri use multimedia-based learning with several objectives and benefits. One aim is to expand knowledge about the history of Islamic culture through the use of multimedia. Media can help learning the History of Islamic Culture at MT by making the material more interesting and interactive and improving the quality of student learning. Several studies have shown that the use of media in learning the History of Islamic Culture at MT has been carried out using various types of media, including sound, audio, visual, images, animation, video, and also words. This shows that this media can improve the quality of student learning.